PENGARUH SUBSTITUSI ABU SEKAM PADI PADA SEMEN DAN ABU BONGGOL JAGUNG PADA AGREGAT HALUS TERHADAP KUAT TEKAN DAN KUAT LENTUR BETON - Alwi, Salma; Dhiva, IGN Aditya; Megawati; Sudibyo, Anung; Prihatin, Kukuh (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
This study aims to investigate the effect of rice husk ash (RHA) as a partial replacement of cement and corn cob ash (CCA) as a partial replacement of fine aggregate on the compressive and flexural strength of concrete at 28 days. The concrete was designed with a target strength of 20 MPa. RHA was used at 6% by weight of cement, while CCA was varied at 4%, 5%, 6%, and 7% by weight of fine aggregate. Testing was performed using cylindrical specimens for compressive strength and beam specimens for flexural strength at 28 days. The control concrete (without additives) had a compressive strength of 10.191 MPa. The addition of 6% RHA and 4% CCA increased compressive strength to 13.135 MPa, rising to 13.531 MPa at 5% CCA, and reaching a peak of 13.701 MPa at 6% CCA, an increase of 34.4% compared to the control. However, at 7% CCA, compressive strength decreased to 12.059 MPa. For flexural strength, the control concrete reached 3.081 MPa, while the highest value of 3.595 MPa was obtained at 7% CCA, an increase of 16.7%. The results indicate that RHA and CCA can improve the mechanical properties of concrete, with different optimum percentages for compressive and flexural strength Keyword: Concrete, Rice husk ash, Corn cob ash, Compressive strength, Flexural strength